Efektivitas Pemakaian Hydrogel terhadap Proses Autolysis Luka Kaki Diabetikum - Hidayat, Rizki; Widowati, Retno; Oktaviana, Nadia (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Diabetic foot ulcers are open wounds on the skin surface due to complications of macroangiopathy that result in vascular insufficiency and neuropathy. Efforts that can be made to treat Diabetic Foot Wounds are to control wounds, infections by routinely cleaning the wound if there is fluid and removing dead tissue. There has been no wound washing intervention using octenidine as a wound washing fluid against biofilms in Diabetic Foot Wounds. Diabetic foot ulcers are a complication that occurs in patients with diabetes mellitus. Patients with diabetic foot wounds in Indonesia are around 15%, with an amputation rate of 30%. Diabetic foot wound care uses a treatment technique using the mouisture balance method which is useful for maintaining moisture in the wound which will cause the autolysis process in the wound so that it can grow new tissue which accelerates wound growth. Hydrogel is a modern dressing that supports wound dressings that can perform autolysis effectively. To identify the effect of octenidine on biofilm among patient with diabetic foot ulcer. Knowing how the effectiveness of the use of hydrogel in diabetic foot wound. This research is a quasy-experiment with a pretest-posttest design approach, namely in this design an initial assessment is carried out through a pretest-posttest. Techniques in conducting samples in this study with a total sampling technique with a total of 20 respondents. This research instrument uses the BWAT assessment sheet. The statistical tests used were univariate and bivariate using paired sample t-tests. The results of the study obtained an average BWAT (Bates-Jansen Wound Assessment Tools) pretest observation score of 36.65 ± 7.85 and a post-test of 24.15 ± 6.95. The results of this study indicate that there is a difference in pretest and post-test BWAT (Bates-Jansen Wound Assessment Tools) assessment scores with a p-value of 0.000. After the use of hydrogel against autolysis in diabetic foot wound patients obtained a p-value of 0.000 so that hydrogel is effective against diabetic foot wound autolysis. Keywords: Diabetic Foot Wound Autolysis, Hydrogel  ABSTRAK Luka kaki diabetikum merupakan komplikasi yang terjadi pada penderita diabetes mellitus. Penderita luka kaki diabetikum di Indonesia berada dikisaran 15%, dengan tingkat amputasi 30%. Perawatan luka kaki diabetikum menggunakan teknik perawatan menggunakan metode mouisture balance yang berguna untuk mempertahankan kelembapan pada luka yang akan menimbulkan proses autolysis pada luka tersebut sehingga dapat menumbuhkan jaringan baru yang mempercepat pertumbuhan luka. Hydrogel merupakan balutan modern yang mendukung pembalut luka yang dapat melakukan autolysis secara efektif. Mengetahui bagaimana efektivitas dari penggunaan hydrogel pada luka kaki diabetikum. Penelitian ini berbentuk quasy eksperimen dengan pendekatan pretest – post-test design yaitu dalam desain ini dilakukan pengkajian awal melalui pretest – posttest. Teknik dalam melakukan sampel dalam penelitian ini dengan teknik total sampling dengan jumlah 20 responden. Instrument penelitian ini menggunakan lembar pengkajian BWAT (Bates-Jansen Wound Assessment Tools). Uji statistik yang digunakan adalah univariat dan bivariat menggunakan paired sample t-test. Hasil penelitian diperoleh rata-rata skor observasi BWAT (Bates-Jansen Wound Assessment Tools) pretest sebesar 36,65 ± 7,85 dan post-test sebesar 24,15 ± 6,95. Hasil penelitian ini menunjukkan bahwa adanya perbedaan skor pengkajian BWAT (Bates-Jansen Wound Assessment Tools) pretest dan post-test dengan nilai p-value 0,000. Setelah penggunaan hydrogel terhadap autolysis pada pasien luka kaki diabetikum didapatkan nilai p-value 0,000 sehingga hydrogel efektif terhadap autolysis luka kaki diabetikum. Kata Kunci: Autolysis Luka Kaki Diabetikum, Hydrogel